Organ-specific metabolic pathways distinguish prediabetes, type 2 diabetes, and normal tissues - Diamanti, Klev; Cavalli, Marco; Pereira, Maria J.; Pan, Gang; Castillejo-López, Casimiro; Kumar, Chanchal; Mundt, Filip; Komorowski, Jan; Deshmukh, Atul S.; Mann, Matthias; Korsgren, Olle; Eriksson, Jan W.; et al. (CELL REPORTS MEDICINE, 2022)
Environmental and genetic factors cause defects in pancreatic islets driving type 2 diabetes (T2D) together with the progression of multi-tissue insulin resistance. Mass spectrometry proteomics on samples from five key metabolic tissues of a cross-sectional cohort of 43 multi-organ donors provides deep coverage of their proteomes. Enrichment analysis of Gene Ontology terms provides a tissue-specific map of altered biological processes across healthy, prediabetes (PD), and T2D subjects. We find widespread alterations in several relevant biological pathways, including increase in hemostasis in pancreatic islets of PD, increase in the complement cascade in liver and pancreatic islets of PD, and elevation in cholesterol biosynthesis in liver of T2D. Our findings point to inflammatory, immune, and vascular alterations in pancreatic islets in PD that are hypotheses to be tested for potential contributions to hormonal perturbations such as impaired insulin and increased glucagon production. This multi-tissue proteomic map suggests tissue-specific metabolic dysregulations in T2D. [Display omitted] •Mass spectrometry proteomics of 5 key metabolic tissues from 43 multi-organ donors•The study provides a map of tissue-specific metabolic dysregulations in PD and T2D•Inflammatory, immune, and vascular processes are altered in pancreatic islets in PD•Lipid and mitochondrial pathways are dysregulated in liver and VAT/muscle in T2D Diamanti et al. map the proteome of five key metabolic tissues of 43 healthy, prediabetes (PD), and type 2 diabetes (T2D) multi-organ donors. The exploration of tissue-specific biological processes indicates that pancreatic islets show multiple biological alterations in PD, while other tissues demonstrate widespread perturbations in T2D.